Understanding terror networks - Sageman, Marc (Univ. of Pennsylvania Press, 2004)
Challenges conventional wisdom about terrorism, arguing that the key to mounting an effective defense against future attacks from Islamist fanatics is a thorough understanding of the networks that allow terrorist operations to proliferate